2013
DOI: 10.2478/s11535-013-0178-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential association of obesity with IL6 G-174C polymorphism and TTV infections

Abstract: Polymorphisms in IL6, ACE and ATR genes are associated with obesity. Torque Teno virus (TTV) seems to be able to interfere with production of some proinflammatory cytokines associated with obesity and related phenotypes. The aim of this study was to test the potential association between obesity, TTV infection and the IL6 G-174C (rs1800795), ACE I/D (rs4646994), AT1R A1166C (rs5186) polymorphisms. The polymorphisms and the presence of TTV were detected in blood samples from 150 obese and 150 normal-weight, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…TTV DNA was more prevalent among obese women without other comorbidities (Pearson’s Chi squared p = 0.024); also BMI of individuals positive for TTV DNA was overall higher than the BMI of TTV DNA-negative individuals (independent sample T-test p = 0.03), nevertheless both observations failed to reach statistical significance following Bonferroni correction. These findings could support and come in addition to previous reports of TTV DNA being more frequent with borderline statistical significance ( p = 0.046) in obese women compared to matched controls [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…TTV DNA was more prevalent among obese women without other comorbidities (Pearson’s Chi squared p = 0.024); also BMI of individuals positive for TTV DNA was overall higher than the BMI of TTV DNA-negative individuals (independent sample T-test p = 0.03), nevertheless both observations failed to reach statistical significance following Bonferroni correction. These findings could support and come in addition to previous reports of TTV DNA being more frequent with borderline statistical significance ( p = 0.046) in obese women compared to matched controls [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our findings here, a number of studies failed to find a significant relationship between TTV prevalence and subject characteristics in other countries, including Egypt [41], Russia [42], Brazil [40], Iran [23] and Qatar [10]. Conversely, a number of studies reported a significant association between TTV prevalence and subject attributes in other countries, including: gender [sic] in the UAE [43]; blood transfusion history in Iran [23]; age in the UK [44], China [19], Brazil [40] and Qatar [10]; and obesity in Romanian women [45].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, TTV was also detected in human lip and kidney tumors [ 103 ]. In studies, TTV load in women with breast cancer showed a significant increase compared to healthy women [ 104 ]. The DNA of TTV has also been identified in the neoplastic tissue of lung cancer and brain tumors, but it is not possible to talk about their relationship with certainty.…”
Section: Human Cancermentioning
confidence: 99%